Psychological support for the talent pathway: Qualitative process evaluation of a state sport academy's psychology service. Issue 3 (4th May 2022) - Keegan, Richard; Stoljarova, Snezana; Kessler, Lena; Jack, Sarah
Abstract: Sport psychologists provide their services in complex settings, with numerous competing demands, resource constraints, and aims/goals for the psychology support service. Research in sport psychology often struggles to characterize the unique challenges of applied practice as it occurs in context. This research examined the delivery of a year-round sport psychology support service in a relatively small state sports academy, which serviced approximately 100 talented and high-potential athletes across multiple sports and levels. A qualitative process evaluation was undertaken. Eight semi-structured interviews were conducted with key stakeholders, including: two current psychologists, one former psychologist, two senior managers, one full time coach and three athletes. After deductively coding content into six higher-order themes, based on process-evaluation approaches, quotes were inductively analyzed using thematic content analysis. Dense and rich category clusters were identified within each higher-order theme: (a) aims and objectives; (b) context and environment; (c) implementation (i.e., what is done by the sport psychologists?); (d) attributes of the sport psychologists; (e) mechanisms of impact; and (f) outcomes generated. The themes extended beyond what is articulated in many current models of service delivery. Analysis suggested that not only are there numerous concepts "in play" when delivering sport psychology services, but that they are deeply interdependent and interconnected. There were notable discrepancies between the assumed aims of the service and the outcomes that were most valued by participants. The study identifies several key strengths and threats for the sport psychology service, and insights that can be applied in diverse service delivery settings. Lay summary: We explored the psychological service delivery of a multi-sport talent development academy, which prepares talented athletes for elite level. We characterized the service's: aims; delivery context; delivery activities; attributes of the deliverer; how outcomes were generated; and outcomes. The analysis emphasized the importance of the competencies, reflexivity and collaboration of practitioner-in-role. Implications for practice: A practitioner in this role requires not only core competencies, but substantial contextual-awareness to tailor service-delivery and manage the expectations of service-users. Many valued outcomes were generated through interdisciplinary collaboration, and not exclusively one-to-one or workshop delivery Protecting the "bandwidth" of such a practitioner—delivering to many service-users largely alone—may facilitate improved outcomes and unexpected opportunities by enabling reflection, planning and collaboration.